Effect of High Fat Diet on Weight Loss Through the Expression of Uncouple Protein 1 in Mice Visceral Fat - Syahraya, Indira; Novida, Hermina; Herawati, Lilik; Rejeki, Purwo Sri (Folia Medica Indonesiana, 2020)
Obesity has become an epidemic around the world. High fat diet (HFD) have been implemented as one of intervention to battle obesity. Uncouple protein 1 (UCP1) is one of the key factor on energy expenditure. The aim of this experiment is to see the macronutrients composition on weight loss and UCP1 expression in the visceral fat. Fifty male mice, 2-3 months old, 18-30 grams, were put in five different groups. K1 were fed (20% protein, 62.0% carbohydrate, 12% fat), K2 (60% protein, 0% carbohydrate, 30% fat), K3 (45% protein, 0% carbohydrate, 45% fat), K4 (30% protein, 0% carbohydrate, 60% fat), K5 (15% protein, 0% carbohydrate, 75% fat). The experiment was done in four weeks, mice body weight was measured every week. UCP1 expression seen using immunohistochemistry staining was measured at the end of the fourth week. Significant weight loss was achieved by K4 (-9.60±3.81) gram by the end of week four (p<0.05). K4 had the least amount of visceral fat. The result was that K4 achieved a significant visceral fat mass (0.02±0.06) gram compared to K1 (0.53±0.08) gram. Compared to other groups K5 expressed UCP1 more than the others (3.78±3.72) cphfp. HFD fed groups produced significant weight loss, group that had the greatest weight loss is K4. Meanwhile, each group had a variety of UCP1 expression.